Perancangan Dan Pembuatan Video Profil Berbasis Produk Pada Prodi Teknik Informatika Politeknik Caltex Riau Menggunakan Teknik Motion Graphic - Firman Danu Ilhamsyah; Juni Nurma Sari (ABEC Indonesia, 2022)
So far, very little information about the final project product of the PSTI (Informatics Engineering Study Program) Caltex Riau Polytechnic, this is evidenced by the results of a survey about the knowledge of the final project product that is produced is still unknown and from the survey conducted shows that 30% know and 70% still do not know, therefore a solution was made so that PSTI can be better known by making a video profile based on the final project product of the 17th generation of PSTI. In making this profile video using motion graphic techniques because by using this technique there are many elements that will be used. The results obtained from the making of PSTI profile videos using motion graphic techniques for the needs of PSTI Caltex Riau Polytechnic as a promotional media have been successfully created, this video helps PSTI to be known by many people through digital media in the form of profile videos, this is proven based on the tests conducted using the Pre-test and Post-test methods, the results obtained showed an increase in understanding of 27.11%, which means that the video media as a promotional medium is very effective as an effort to promote PSTI Caltex Riau Polytechnic.